Анализ концепта «работа» (на материале французского и украинского языков) - Норец, Т.М. (Культура народов Причерноморья, 2013)
В статье описывается методика применения семантико-когнитивного анализа при
изучении ключевых концептов различных лингвосоциумов. Предметом сопоставительного исследования
является концепт «работа» во французском и украинском языках. Сопоставление проводится по двум
параметрам: историко-этимологическому и паремиологическому. Результаты анализа убедительно
показали возможность объяснения тематического расхождения паремий разных языков исходя из
этимологических данных, которые лежат в основе формирования концептов. В статті описується методика застосування семантико-когнітивного аналізу при вивченні
різних лінгвосоціумів. Предметом зіставного дослідження є концепт «робота» французькою та
українською мовами. Зіставлення здійснюється за двома параметрами: історико-етимологічним і
пареміологічним. Результати аналізу переконливо показали можливість пояснення тематичної
розбіжності паремій різних мов на підставі етимологічних даних, які є основою формування концептів. The article deals with the semantic and cognitive analysis of the key concepts in different lingual
societies. The object of the comparative analysis is concept “work” in French and Ukrainian languages. Two
parameters are taken into consideration while comparing: etymological and paremiological. The results of the
research show that the comparative analysis which is based on etymological data, influencing the concept
formation, helps to explain the thematic differences of proverbs and sayings in different languages. The notion
concept is realized through different language means and gives the possibility with the help of investigating the
peculiarities of nomination, morphology and wordbuilding, valency and combinability of language units,
paremiological and phraseological data to penetrate into the language competence of the society. Using the
semantic-cognitive analysis lets take the knowledge of the world out of meanings; the knowledge which was fixed
in them and is the result of the process of learning the surrounding (social or natural) by people.